Risk Factors of Bacteremia following Multiple Traumas - Hak-Jae Lee; Eol Choi; Nak-Joon Choi; Hyun-Woo Sun; Jae-Suk Lee; Jeong-Woo Lee; Tae-Yoon Kim; Yoon-Joong Jung; Suk-Kyung Hong (Emergency Medicine International)
Background. Bacteremia is a major nosocomial infection that frequently occurs in trauma patients, increasing morbidity and mortality. The aim of this study was to identify risk factors and to describe epidemiological patterns for early onset (EOB) and late onset (LOB) bacteremia after trauma. Methods. We retrospectively reviewed medical records of all trauma patients admitted to the surgical intensive care unit and general ward between January 2011 and December 2015. The information was collected for each patient and recorded in a computer database: early onset bacteremia (EOB) was defined as when onset occurred within 7 days after trauma, and late onset bacteremia (LOB) was defined as when onset occurred after 7 days from trauma. Results. Thirty-four patients of 859 (4%) developed bacteremia during their hospital stay: 4 (11.8%) developed EOB, 26 (76.4%) LOB, and 4 (11.8%) patients developed both of them. Sixty events of bacteremia happened to these patients: 9 (15.0%) EOB and 51 (85.0%) LOB. Gram-positive cocci were isolated more frequently than Gram-negative bacilli in both groups. Gram-positive cocci were more frequently isolated in EOB than in LOB; otherwise, there was no statistical significance (77.8% vs. 64.7%, p=0.683). Central line-associated blood stream infection (CLABSI) and surgical site infection (SSI) were the most common identified source for LOB. Presence of liver (OR: 2.66, p=0.035) and pelvic injury (OR: 2.25, p=0.038), gastrointestinal tract perforation (OR: 5.48, p=0.002), and massive transfusion (OR: 3.36, p=0.006) represented risk factors for bacteremia. Conclusions. Presence of pelvic and liver injury on arrival in emergency department, gastrointestinal tract perforation, and massive transfusion within the first 24 hours after trauma appears to be significant risk factors for bacteremia.